Makki dan Madani Serta Beberapa Diskusi Tentangnya - Hj. Yusoff, Zulkifli (Jurnal Usuluddin, 1995)
Al-Quran is not only the holy "Kitab" for the Muslim, but it’s also a rule and a way of life for man. The "surahs" in al-Quran was revealed in Mecca and Medina and known as "surah Makki" and "surah Madani". Therefore this article attempts to look into the meaning of these surah according to "ulama" and the methodology to ensure these "surah" as Makki" and "Madani".